Body Motion Auto Tracking Camera System for Online Class Education Supporting Device Using OpenCV and Microcontroller - Tia, Rahmawati; Denny, Darlis; Atik, Novianti (INTI International University, 2024)
In the online teaching process, a teacher is necessary to describe the material clearly and have a broad perspective so that the material can be delivered completely. The problem occurs because the camera has different viewing angles, which results in limited movement of people who are teachers whenever explain material on a broad chalkboard. For this reason, a motion tracking camera is designed like a common camera that can move to follow the teacher's upper body. The camera will be connected to servo motors such as MG996R to move the camera on the X-Axis and Y-Axis. Then with OpenCV technology, the camera will track the teacher as an object and follow the direction of his/her movement. The results from thisresearch, it is concluded that by integrating Python into a video conference application and without it, the system can detect the upper body at 2-6 meters. For the X-Axis servo motor angle for conditions using video conference and without video conference application, the servo can rotate by detecting the upper body at angles of 30deg, 60deg, 90deg, 120deg, and 150deg. Then on the Y-Axis movement, it can rotate by detecting the upper body at 90deg, 100deg, 110deg, 120deg and 130deg angles. The test was carried out in a room with an area of 9.1 m x 7.4 m, the light condition of the room was 116 lux the object height was 1.5 m, and the camera height was 0.8 m above the floor